Depression Level Among Neurology Resident Doctors in the Faculty of Medicine, Universitas Indonesia - Dyah Perwitasari, Vina; Hidayat, Rakhmad (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2024)
Introduction: A resident doctor is a doctor who has graduated from medical school, has earned the title of